The Impact of Foreign Direct Investment (FDI) on Economic Growth in Developing Countries to Acceleration in Digitalization - Supriyanto, Supriyanto; Widayani, Hapsari; Riri Cornellia; Rini Armin; Irsyad Kamal (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of Foreign Direct Investment (FDI) on regional economic growth in Indonesia through digitalization acceleration. Using a mixed-methods approach with a sequential explanatory design, the research was conducted in four provinces representing variations in digital readiness and FDI acceptance: West Java, East Java, South Sulawesi, and East Kalimantan. The quantitative results were analyzed using SEM-PLS regression, while the qualitative findings were examined through thematic coding. The study found that FDI significantly contributes to regional digitalization and has a positive impact on economic growth; however, this effect is significantly strengthened by local digital readiness. Digitalization proves to be an important mediator in enhancing the relationship between FDI and economic growth, particularly in terms of operational efficiency, expanding MSME markets, and technological innovation. Digital readiness disparities between regions act as limiting factors, where areas with weak ICT infrastructure and human resources show lower impacts. Therefore, cross-sector collaborative strategies involving local governments, academics, MSME actors, and foreign investors are necessary to build an inclusive and sustainable digital ecosystem. The research highlights the importance of data-driven policy design and local capacity building as prerequisites to maximize the economic benefits of digital-based FDI. These findings are expected to serve as a reference for policymakers, business actors, and researchers in supporting responsive and competitive regional digital economic transformation.